Comparisons of Weekly Hours over the Past Century and the Importance of Work-Sharing Policies in the 1930s - Neumann, Todd C; Taylor, Jason E; Fishback, Price (American Economic Review, 2013)
Changes in the work week drove a larger portion of changes in total labor input during the Great Depression of the 1930s than during other decades. Work-sharing policies appear to be responsible. Herbert Hoover created various work-sharing committees–led by key industrialists–which pushed for shorter work weeks. And Franklin Roosevelt's President's Reemployment Agreement called for sharp cuts in weekly work hours. Spreading available work amongst more people was the goal. During these periods between 50 and 90 percent of declines in labor input were accommodated by falling hours. In recent decades employers have instead relied on layoffs to achieve the same end.